Increasing Prevention Knowledge of Sexual Violence and Emotional Maturity on Children through the Mini-Movie Media - Iqlima Dwi Kurnia; Ilya Krisnana; Farida Norma Yulianti (Faculty of Nursing Universitas Padjadjaran, 2020)
Sexual violence against children is one of the world’s problem that has an impact on the mental, physical, and psychological conditions such as depression, fear, shame, which can lead to suicide for the victim. The level of prevention knowledge and emotional maturity in the child needs to be grown. Objective of this study was analyze the effect of mini movie on the level of knowledge prevention of sexual violence and the level of emotional maturity in school-age children. Mini movie video according to research by the American Psychological Association (APA) is an audio-visual media with message conveyed in the form of short films through hearing and sight. Mini movie contains 2 video, the first video taken from UNICEF Indonesia. The second video came from center for study and child protection (PKPA). This study used quasi experimental design with two groups and involved 85 students. The Emotional Maturity and Knowledge of Child Abuse Questionnaire used as the instrument. This research conducted used a simple random sampling technique. The research showed that mini movie media had a significant impact on the level of prevention knowledge sexual violence (p=0.000) and the level of emotional maturity (p=0.000) Mini movie media becomes a mass approach in modern era that can provide accurate information in delivering health messages for children. Education through mini movie media can stimulate children’s awareness and teacher as an effort to prevent sexual violence by increasing children’s knowledge and emotional maturity.